An Ab Initio Study of the Ground and Low-Lying Excited States of $LiBe^+$ (Journal of Atomic and Molecular Sciences, 2015)
By using multi-reference configuration interaction method and large all-electronbasis sets aug-cc-pwCV5Z, we have calculated the dense potential energycurves (PECs) of $1¹Σ^+,$ $1³Σ^+,$ $1¹Π,$ and $1³Π$ states of $LiBe^+$ molecule. Based on the obtainedPECs, the analytical potential energy functions (APEF) have been constructedwith a Morse long-range potential function and nonlinear least squares method. Therotational and vibrational energy levels of the four states are determined by solvingSchrödinger equation of nuclear movement with the APEFs. The spectroscopic parametersare deduced with the obtained rotational and vibrational energy levels.
Keywords: analytical potential energy function; excited state; spectroscopic parameters.